CONTENTS DIPHTHERIA ANTITOXIC AND ANTIBACTERIAL ANTIBODIES IN THE SERUM OF HEALTHY ADULTS - E. A. Shmeleva; S. M. Popkova; T. N. Flrsova; E. B. Rakova; L. V. Serdyuk; M. M. Gubin (Acta Biomedica Scientifica, 2012)
In the article using the binomial distribution analysis of the intensity of рориlation antitoxic (AT) and antibacterial (AB) of immunity to diphtheria in terms of specific diphtheria antibodies in the sera of healthy adults aged 20 to 51 years and. older, living in Russia and. Italy. The latter, in contrast to Russia, during the epidemic was only a few cases of diphtheria. For the population of people from Italy the optimal parameters of tension antibody immunity (bimodal distribution of the concentrations of AT antibodies) are determined, whereas for the adult population of Russia experienced an abnormally high, overvoltages antibody immunity (lack of bimodal distribution). The level of concentration of antibody isotypes AB M, G, A in both countries match the total synthesis of immunoglobulin isotypes in the ontogeny of these: thus, in the sera of adults aged 20 to 40 years AB antibody IgG prevail. Low concentrations of antitoxin in the blood of most adults living in Italy, recharged high AB IgG in these same serum, and. optimal concentrations of AB IgM and. IgA. This indicates the possibility lifting the mass revaccination of adults, and. creating an individual approach to their boosters. Optimal bimodal distribution of AB antibodies in the population of healthy adults, both in Russia and. in Italy, is an additional protection to the diphtheria antitoxic resistance.